Martina Blečić, Matija Črešnar, Bernhard Hänsel, Anja Hellmuth, Elke Kaiser and Carola Metzner- Nebelsick (eds.): Scripta praehistorica in honorem Biba Teržan, 2007 - Megaw, J. V. S. (Arheološki vestnik, 2009)
/